'Studies in stability and control analysis of airframes having nonlinear aerodynamic characteristics' - Christopher, P. A. T. (College of Aeronautics, 1966)
The problem of longitudinal stability and control of an airframe, having nonlinearity in its principal aerodynamic characteristics, is considered. It is shown that the equation describing the response in w, and thus the incidence, is a nonlinear differential equation of the fourth order. This equation, and its degenerate forms, is used as an example to demonstrate various nonlinear techniques and their shortcomings.